KOMUNIKASI MULTIKULTURAL SANTRI DALAM MEMAHAMI MAKNA ARAB JAWA PEGON DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Afif Mahmudi (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2023)
The Darussalam Banyuwangi Islamic Boarding School in the process of interpreting the cleric's book uses a distinctive language, namely refined Javanese (kromo inggil), even though the background of the students do not only come from Java but in various regions in Indonesia, and some even come from abroad. This reality made the researcher interested in raising the research title of the Multicultural Communication Patterns of Santri in Understanding Javanese Arabic (Pegon) at Darussalam Islamic Boarding School Blokagung Banyuwangi. The purpose of this study is to describe the Multicultural Communication of Santri in Understanding the meaning of Javanese Arabic (Pegon) at Pondok Pesantren Darussalam Blokagung Banyuwangi. The method used by researchers to uncover these questions is a descriptive qualitative approach. The results obtained by this study are the pattern of Multicultural Communication of Santri Darussalam Blokagung Islamic Boarding School originating from outside Java to understand the meaning of the yellow book is by communicating the exchange of meanings between individuals by using Indonesian as an alternative language. The intensity of communication between junior students and senior students gave birth to a similarity in meaning, perception, motivation, and the respective Javanese vocabulary used in interpreting the yellow book is always asked by junior students to senior students.